Proszę wsiadać drzwi zamykać!. (Gdańsk : [s.n.], 1950)
Afisz inf. o koncercie w sali Teatru Wybrzeże w gdańskim Wrzeszczu 1.10.1950 r.
Keywords: Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- życie artystyczne